2006
DOI: 10.4049/jimmunol.177.2.1229
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Responses toPlasmodiumInfection and Control of Intrahepatic Parasite Development

Abstract: Various components of innate and adaptive immunity contribute to host defenses against Plasmodium infection. We investigated the contribution of NK cells to the immune response to primary infection with Plasmodium yoelii sporozoites in C57BL/6 mice. We found that hepatic and splenic NK cells were activated during infection and displayed different phenotypic and functional properties. The number of hepatic NK cells increased whereas the number of splenic NK cells decreased. Expression of the Ly49 repertoire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 65 publications
7
62
0
2
Order By: Relevance
“…Thus, the inability to control lethal P. yoelii infection is only minimally affected by the absence of T cells and/or B cells with clonally rearranged antigen receptors. Moreover, and in agreement with previous studies in T-and B-cell-deficient animals (6,12,42), the course of PyNL infection in RAG Ϫ/Ϫ mice did not differ either significantly or reproducibly from that in WT mice up to 10 days p.i., indicating that antigen-specific T cells do not contribute significantly to control of the primary wave of parasitemia in nonlethal P. yoelii infection. As previously shown, however, RAG Ϫ/Ϫ mice were unable to control their infections over the long term with parasitemia rising steadily over a period of weeks (Fig.…”
Section: P Yoelii-induced T-cell Hyporesponsiveness Is Both Cd11bsupporting
confidence: 78%
See 3 more Smart Citations
“…Thus, the inability to control lethal P. yoelii infection is only minimally affected by the absence of T cells and/or B cells with clonally rearranged antigen receptors. Moreover, and in agreement with previous studies in T-and B-cell-deficient animals (6,12,42), the course of PyNL infection in RAG Ϫ/Ϫ mice did not differ either significantly or reproducibly from that in WT mice up to 10 days p.i., indicating that antigen-specific T cells do not contribute significantly to control of the primary wave of parasitemia in nonlethal P. yoelii infection. As previously shown, however, RAG Ϫ/Ϫ mice were unable to control their infections over the long term with parasitemia rising steadily over a period of weeks (Fig.…”
Section: P Yoelii-induced T-cell Hyporesponsiveness Is Both Cd11bsupporting
confidence: 78%
“…Nevertheless, despite the distinct differences in NK cell and IFN-␥ responses evident during lethal and nonlethal P. yoelii infections, NK cell-depleted mice, although displaying slightly accelerated parasite numbers during lethal infection, did not display either increased ascending or peak parasite numbers during nonlethal infection, and IFN-␥ Ϫ/Ϫ mice were as susceptible or resistant to lethal or nonlethal infection, respectively, as WT mice were. Although it has previously been reported that NK cells are required for optimal resistance to PyNL in F 1 hybrid BALB/c ϫ C57BL/6 mice and in CB17 SCID mice (6, 10), a recent study in RAG Ϫ/Ϫ common ␥-chain Ϫ/Ϫ double knockout mice on a C57BL/6 background did not show a major role for NK cells during blood-stage PyNL infection (42). Additionally, a number of studies have provided conflicting reports on the importance of IFN-␥ during P. yoelii infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although natural killer (NK) cells have been studied most extensively in terms of viral and tumour immunity, there is an increasing awareness that NK cells are activated, and in some situations potentially have a protective role, in immune responses to certain microorganisms, including Legionella pneumophila 109 122 and Plasmodium falciparum (reviewed in REF. 123 ).…”
Section: Box 1 Nk Cells In Immunity To Microbial Pathogens Other Thanmentioning
confidence: 99%